Translation Analysis on Syafira’s Novel 'Kado Misterius Volume 3' - Emianto, Rizki Ananda; Setiawan, Kristianto; Sudja'ie, Mimien Aminah (Jurnal Vokasia, 2022)
This article is entitled Translating Syafira's Novel Kado Mysterious Volume 3 from Indonesian into English. The purpose is to provide an English version of the children's novel Kado Mysterius because it has an exciting storyline and meaningful messages. Therefore, this novel deserved to be appreciated and introduced as Indonesian literary work to people around the globe. The translation process applied some steps; the Analysis step, the Transfer step, and the Restructuring step. However, several obstacles were found in translating the novel Kado Mysterious; first, the translator found it challenging to find relevant terms in the target language. Then, the translator had limited knowledge of some original or target language words. Moreover, the solutions to overcome these obstacles were applied; first, some terms were searched, studied, and consulted to proofreaders to find the relevant meanings. And the translator also used a dictionary to look up new words found in the original language. Experience and knowledge were gained while working on this report, such as getting new vocabulary, knowing translation techniques, the methods needed, and the stages of the translation process. In addition, applying the proper solution was the answer to easily overcome the obstacles during the translation process.